Effects of recycled Fe2O3 nanofiller on the structural, thermal, mechanical, dielectric, and magnetic properties of PTFE matrix - Khamis, Ahmad Mamoun; Abbas, Zulkifly; Azis, Raba'ah Syahidah; Mensah, Ebenezer Ekow; Alhaji, Ibrahim Abubakar (Multidisciplinary Digital Publishing Institute, 2021)
The purpose of this study was to improve the dielectric, magnetic, and thermal properties of polytetrafluoroethylene (PTFE) composites using recycled Fe2O3 (rFe2O3) nanofiller. Hematite (Fe2O3) was recycled from mill scale waste and the particle size was reduced to 11.3 nm after 6 h of high-energy ball milling. Different compositions (5–25 wt %) of rFe2O3 nanoparticles were incorporated as a filler in the PTFE matrix through a hydraulic pressing and sintering method in order to fabricate rFe2O3–PTFE nanocomposites. The microstructure properties of rFe2O3 nanoparticles and the nanocomposites were characterized through X-ray diffraction (XRD), field emission scanning electron microscopy (FESEM), and high-resolution transmission electron microscopy (HRTEM). The thermal expansion coefficients (CTEs) of the PTFE matrix and nanocomposites were determined using a dilatometer apparatus. The complex permittivity and permeability were measured using rectangular waveguide connected to vector network analyzer (VNA) in the frequency range 8.2–12.4 GHz. The CTE of PTFE matrix decreased from 65.28×10−6/°C to 39.84×10−6/°C when the filler loading increased to 25 wt %. The real (ε′) and imaginary (ε″) parts of permittivity increased with the rFe2O3 loading and reached maximum values of 3.1 and 0.23 at 8 GHz when the filler loading was increased from 5 to 25 wt %. A maximum complex permeability of (1.1−j0.07) was also achieved by 25 wt % nanocomposite at 10 GHz.